A crítica de Mandelbrot: normalidade como exceção e não como regra - Barbosa, Bruno Teixeira Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Starting with a brief introduction about the evolution of asset pricing models, we seek here to introduce the critique made by Benoit Mandelbrot about using the normality hypothesis when building such models. This critique arises when empirical and theoretical models where confronted and the expected results diverged from the ones obtained. Next, we reproduce Mandelbrot alternative which he believes is sufficient to solve the main problems implied by the normality hyphotesis

A partir de uma introdução sucinta sobre a evolução dos modelos de precificação de ativos, busca-se aqui introduzir a crítica feita por Benoit Mandelbrot à utilização de hipóteses de normalidade para modelos de precificação de ativos baseada principalmente na divergência teórica e empírica entre problema propostos e resultados esperados, e aqueles encontrados empiricamente. A seguir, propõe-se uma alternativa que tenta resolver alguns dos problemas implicados pelas hipóteses tradcionalmente assumidas
Mandelbrot’ critique: Normality as an exception and not as a rule
Keywords: Mandelbrot, Benoit B. 1924; Balanço (Contabilidade); Economia; Economics